2022
DOI: 10.1186/s12978-021-01276-8
|View full text |Cite
|
Sign up to set email alerts
|

Women's strategies for managing domestic violence during pregnancy: a qualitative study in Iran

Abstract: Background Domestic violence during pregnancy is a severe public health problem. Abused pregnant women are confronted with the threats posed by domestic violence. Pregnancy and protection of the unborn child could affect maternal strategies for managing violence. The purpose of this study was to explore Iranian women's strategies for managing domestic violence during pregnancy. Methods This qualitative study was conducted in October 2019 to June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
3
8
1
Order By: Relevance
“…It is reported that fear of the perpetrator negatively affects support seeking (79) . The current findings are contrary to the study by Amel Barez et al (80) where the bulk of the women never asked for help and kept their experiences with perinatal IPV hidden..…”
Section: Discussioncontrasting
confidence: 99%
“…It is reported that fear of the perpetrator negatively affects support seeking (79) . The current findings are contrary to the study by Amel Barez et al (80) where the bulk of the women never asked for help and kept their experiences with perinatal IPV hidden..…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, it is essential to implement appropriate policies to support mothers and reduce violent behaviors toward them in households ( 38 ). In line with the present study Amel Barez et al ( 3 ) also stated that it is evident that violence against pregnant women is relatively high in Iran. Abusive behaviors are associated with mothers’ financial, mental health, educational, and occupational status.…”
Section: Discussionsupporting
confidence: 92%
“…Pregnant women resort to strategies such as improving their situation or escaping from conditions that lead to violence to protect themselves and their infants. Policymakers need to enforce stricter laws to protect the rights of women and pregnant mothers, as well as children with disabilities, and carefully follow up on cases of violence against them and impose appropriate penalties ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional content analysis approach was used to explain the research question. The data were simultaneously analyzed with data collection, using Graneheim and Lundman method which allows the researchers to examine individual experiences and shows conflicting opinions and unsolved issues regarding the meaning and use of concepts, procedures and interpretation [ 36 , 42 , 43 ] by MAXQDA software (version 10, VERBI Software, Berlin, Germany). After each interview, the first author listened to the interviews several times to obtain a general perspective of their content, and then transcribed the interviews verbatim and read it several times to gain an overall understanding of their content.…”
Section: Methodsmentioning
confidence: 99%